Peran Guru Akidah Akhlak Dalam Mencegah Akhlak Mazmumah Siswa Kelas X MAN 2 Tapin - Ulfah, Emilya (Darussalam, 2025)
The background of this research is the effect of globalization which has brought changes in attitudes in positive and negative forms and can have an impact on students' poor behavior or bad morals. The role of the moral akidah teacher is very necessary in preventing mazmumah morals from occurring in class X MAN 2 Tapin. The author aims to determine the role of moral akidah teachers in preventing mazmumah morals; and knowing the supporting factors in preventing mazmumah morals in class t MAN 2 Tapin. The data collection technique used is through observation, interviews and documentation. Data analysis uses qualitative descriptive analysis and in drawing conclusions uses an inductive method. The results of the writing show that the role of akhkak akidah teachers in preventing students' mazmumah morals is carried out by educating, guiding, directing, advising and motivating them to run well. Supporting factors in preventing mazmumah morals are that the teacher has a good educational background, the teacher has experience, and the teacher has also attended training/seminars.